STUDI PEMIKIRAN TOKOH ORIENTALIS (IGNAZ GOLDZHIER) TERHADAP KEOTENTIKAN HADITS - Fathoni, Imam; Ulfiah, Umi Hanik (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
The authenticity of the hadith of the Prophet s.a.w. seems to be undoubted in his belief among Muslims. However, the study of the authenticity of this hadith is a topic that is always discussed. Especially the errors or mistakes from the hadith are very sought by the orientalists. The purpose of this article is to know Ignaz Goldziher's thoughts on the authenticity of the Hadith. The results of this study are: Ignaz Goldziher's thoughts in examining the authenticity of the hadith, namely: first, What can be justified from the lifetime of Muhammad PBUH is the Quran. Others, including hadiths made by Muslims from the second and third centuries AH/VIII and IX AD. Second, Goldziher argues that the hadith as a whole is the product of people who lived in the second or early third century of the Hijri and is not the utterance of the Prophet (peace be upon him), because the sharia laws were unknown to Muslims in the first period of Hijri.